PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN SENI BUDAYA DI SEKOLAH DASAR - Julia, Mona; Wiwin Winarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is the awareness of individuals in growing and developing the potential of human resources through teaching activities. One of the factors that determines the success of the teaching and learning process is learning motivation. In learning activities, motivation is the overall driving force in the self that gives rise to learning activities that ensure the sustainability of learning activities (Widhayanti et al., 2021). Today, many students are less motivated to learn. This can be seen from the attitude of students who do not care about the learning process, do not pay attention to the teacher when explaining the material and do not do the assignments given by the teacher. Learning activities can be said to be successful with one of the factors, namely the role of teachers. According to (Soeharni, 2021) teachers are the supervisors of the learning journey who are responsible for the smooth learning of students. This study uses a literature review approach, which is a research method that is carried out by examining various references or reading sources related to the topic of discussion. These references include scientific journals, educational articles, e-books, and research results This motivation also plays a role in fostering positive attitudes such as enthusiasm and love to learn so that it can improve students' knowledge and skills. Education is the awareness of individuals in growing and developing the potential of human resources through teaching activities.In the history of education, teachers are respected and considered as the main figures in shaping attitudes, developing competencies, and developing social interaction through learning.